2022
DOI: 10.3390/su14084710
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Criteria of Flax Fiber (Linum usititassimum L.) as Influenced by Different Plant Densities

Abstract: Flax (Linum usitatissimum L.) is mostly grown in temperate climate conditions. The rising demand for natural fibres other than cotton has re-introduced flax cultivation in to the agenda. This situation has necessitated the acceleration of flax production research in Turkey. The purpose of this research is to discover the best seeding density for flax fibre cultivation. The trials were carried out with the Rolin flax variety at the coordinates 41°21′53″ N and 36°11′17″ E, during the winter seasons of 2018–2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…[23], in a pot experiment conducted with three different levels of Cd, Ni, Pb, and Sb in three flax cultivars, concluded that as the dose of the metal and antimony increased, the growth characteristics of the varieties decreased. The mean values of the height recorded in our study align with those reported in other field non-polluted experimental studies, resulting in similar average height values for flaxseed [57,59,69]. Ref.…”
Section: Discussionsupporting
confidence: 91%
“…[23], in a pot experiment conducted with three different levels of Cd, Ni, Pb, and Sb in three flax cultivars, concluded that as the dose of the metal and antimony increased, the growth characteristics of the varieties decreased. The mean values of the height recorded in our study align with those reported in other field non-polluted experimental studies, resulting in similar average height values for flaxseed [57,59,69]. Ref.…”
Section: Discussionsupporting
confidence: 91%
“…[6], in pot experiment that conducted with three different level of cadmium, nickel, lead and antimony in three flax cultivars, concluded that as the dose of the metal and antimony increased, the growth characteristics of the varieties decreased. The mean values of the height recorded in our study align with those reported in other field non-polluted experimental studies, resulting similar average height values for flaxseed [25,27,37]. [25] highlighted the aspect of the growing cycle duration, reporting taller linseed plants (62.9 cm) during autumn sowings compared to spring sowings (55.5 cm) in a semi-arid Mediterranean environment.…”
Section: Discussionsupporting
confidence: 89%
“…Previous researches underline the complex interaction of factors that impact flax development, such as residual soil nitrogen, soil type, flax cultivar, climate and moisture conditions, and growing cycle duration [10,14,[22][23][24][25][26]. Furthermore, the key roles of plant density, climatic conditions, and nitrogen levels in shaping stem branching in flaxseed have been emphasized in various studies [25][26][27][28][29][30]. Understanding the importance of these factors is crucial when evaluating flax branching patterns, as they significantly affect plant architecture and yield.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this decrease may be due to the increased competition among plants for light and nutrients, resulting from an increased number of plants per unit area. This result agrees with the findings of [17,18], who reported a significant decrease in stem diameter of flax with an increase in seeding rate. Furthermore, the results show that variety Sakha 6 achieved the highest mean stem diameter of 2.56 mm, which was not significantly different from variety Sakha 4 but was significantly different from the local variety, which had the lowest mean stem diameter of 2.40 mm.…”
Section: Stem Diameter (Mm)supporting
confidence: 93%